Association Between Dietary Fatty Acid Pattern and Risk of Oral Cancer - Fan, Yi; Qiu, Yu; Wang, Jing; Chen, Qing; Wang, Sijie; Wang, Yaping; Li, Yanni; Weng, Yanfeng; Qian, Jiawen; Chen, Fa; Wang, Jing; Shi, Bin; et al. (Frontiers in Nutrition, 2022)
Objective: To investigate the association between dietary fatty acid patterns and the risk of oral cancer. Method: A case-control study which included 446 oral cancer patients and 448 controls subjects was conducted in Southeast China. A structured food frequency questionnaire was used to assess dietary fatty acid consumption before cancer diagnosis. Fatty acid patterns were identified using principal component analysis, and the relationship between dietary fatty acid patterns and oral cancer was analyzed by logistic regression. Results: General differences in fatty acid intake were observed between the patient and control group. Intake of saturated fatty acids C14:0, C16:0, C18:0 and monounsaturated fatty acid C18:1 were higher in the patient group than the control group (p<0.001). Four fatty acid patterns were derived by principal component analysis. The “Saturated fatty acid” pattern, “Polyunsaturated fatty acid” pattern, “Monounsaturated fatty acid” pattern, and “Medium- and long-chain fatty acid” pattern, which could explain 75.7% of the variance of the dietary fatty acid intake, were submitted to logistic regression analysis. A positive association was observed between the “Saturated fatty acid” pattern and oral cancer risk. Compared with the lowest quartile score, the OR of the highest quartile score was 3.71 (95%CI: 2.31, 5.94, Ptrend<0.001) in the multivariate logistic regression model. No significant association was found between the other three patterns and oral cancer risk. Conclusions: General differences in dietary fatty acids intake were observed between oral cancer patients and controls. Positive association between the “SFA” pattern and risk of oral cancer was observed after adjusting for potential confounders.